Analisa Hilang Daya Pada Generator Sinkron 3 Fasa (6,6 KV) 11 MVA TYPE 1DT4038-3EE02-Z - RAHMAT SEPTIYAN; Mayda Waruni K; Bambang Sugeng (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
The loss of power in a 3 phase synchronous generator is caused by losses on the generator consisting of copper loss, mechanical loss, core loss and stray load loss. power loss analysis on the 3 phase synchronous generator is carried out to measure the ability or performance of the generator to the load. The method used is qualitative and calculations with mathematical analysis based on measurements or data obtained. the total loss of power at the generator from the calculation is at a 25% load of 172,218 kilowatts, a 50% load of 190,102 kilowatts, a 75% load of 218,393 kilowatts and a 100% load of 257.56 kilowatts. and with a value of power output at a 25% load of 2,110 kilowatts, a 50% load of 4,398 kilowatts, a 75% load of 6,598 kilowatts and a 100% load of 8,797 kilowatts. the percentage of efficiency or performance on the generator is 92.4% at 25% load, 95.8% at 50% load, 96.7% at 75% load and 97.1% at 100% load.